On the Difference Equation xn+1=∑j=0kajfj(xn−j) - Stevo Stevic (Discrete Dynamics in Nature and Society)
This paper studies the boundedness character and the global attractivity of positive solutions of the difference equation xn+1=∑j=0kajfj(xn−j),n∈ℕ0, where aj are positive numbers and fj are continuous decreasing self-maps of the interval (0,∞) for j=0,1,…,k.